Answer:
y = -5x + 4
Step-by-step explanation:
y=Mx+b
Answer:
15
Step-by-step explanation:
After plugging in the 6, multiply 2 and 6 and then add 3. This equals 15.
5/6(x-1)=4
(x-1)=(4*6)/5
x-1=24/5
x=24/5 + 1
least common multiple=5
x=(24+1*5)/5
x=29/5
Answer: x=29/5
To check:
5/6(x-1)=5/6(29/5 -1)=5/6[(29-5)/5]=5/6(24/5)=(5*24)/(6*5)=120/30=4
Always eliminate the first one before moving on. Remember to drop down monomials, like you would a normal division problem.
2x² + 10x + 18
__________________
x + 3 | 2x³ + 16x² - 12x + 9
-(2x³ + 6x²)
-------------------------------
10x² - 12x
-(10x² - 30x)
-----------------------------
+ 18x + 9
- (18x + 54)
----------------------
-45
2x² + 10x + 18 R: -45/x + 3 is your answer R: = remainder
hope this helps